The glittering court ebook - Mead, Richelle (The Glittering Court, 2016)
A #1 NEW YORK TIMES BEST SELLER The Selection  meets  Reign  in this dazzling trilogy of interwoven novels about three girls on a quest for freedom and true love from #1 internationally bestselling author Richelle Mead. "Brilliant and original, Mead’s new series starts off with a bang and will leave readers on the edge of their seats until the very end." — School Library Journal   For a select group of girls, the Glittering Court offers a shot at a life they’ve only ever dreamed of, one of luxury, glamour, and leisure. To high-born Adelaide, whose wealthy family is forcing her into a loveless marriage, the Glittering Court represents something else: the chance to chart her own destiny, and adventure in an unspoiled, prosperous new land across the sea.   After a chance meeting with the dazzling Cedric Thorn, Adelaide poses as a servant to join the crop of impoverished girls he promises to transform into proper ladies. But her familiarity with upper class life comes with a price: she must hide her identity from her new friends, mysterious refugee Mira and fiery former laundress Tamsin, and most importantly, from Cedric himself—even though she’s falling in love with him.    Everything begins to crumble when Cedric discovers Adelaide’s ruse, and she catches the eye of a powerful young governor, who wants her for a wife. She didn’t leave the gilded cage of her old life behind just to become someone else's property. But nothing is as daunting—or as wonderful—as the potent, forbidden attraction simmering between Adelaide and Cedric. One that, if acted on, would make them both outcasts in a wild, dangerous, uncharted world, and possibly lead them to their deaths.